Challenges and Difficulties of Spinal Anesthesia in a Patient with Traumatic Thoracolumber Scoliosis - Tanzil, Tasnuva; Khatoon, Syeda Nafisa; Dhar, Satyajit; Alam, AKM Samsul (Journal of the Bangladesh Society of Anaesthesiologists, 2021)
We report an interesting and challenging case of traumatic thoracolumber scoliosis presenting with closefracture of right patella planned for open reduction and internal fixation (ORIF) under regional anesthesia.However, spinal anesthesia was not successful even with the use of intra operative fluoroscopy or ultrasoundguidance. We have in view to show the importance of proper review of preoperative x-ray of dorsolumberspine scoliosis and careful physical examination of back of the patients by the anesthesiologist to administeran effective and safe spinal anesthesia in such patients in low resource setting for successful & safe spinalanesthesia. JBSA 2021; 34(1): 54-56